RAPD and rep-PCR fingerprinting for characterization of Bifidobacterium species - Křížová, Jana; Španová, Alena; Rittich, Bohuslav (Folia microbiologica, 2008)
DNA fingerprinting methods, RAPD with 7 random primers, and rep-PCR using both BOXA1R and (GTG)(5) ones, were used for the discrimination of 16 type and collection Bifidobacterium strains of 9 species of human origin, B. animalis ssp. animalis and B. animalis ssp. lactis and 7 Bifidobacterium strains collected in the Culture Collection of Dairy Microorganisms (CCDM). Both RAPD and rep-PCR methods provided similar results. The strains were identified as B. animalis ssp. lactis (6 strains) and B. adolescentis (1 strain). The reclassification of the collection strain CCM 3761 as B. pseudocatenulatum species (previously classified as B. adolescentis) was confirmed.
Keywords: Animals; Bifidobacterium; techniky typizace bakterií; Humans; DNA, Bacterial; Phylogeny; lidé; zvířata; fylogeneze; Random Amplified Polymorphic DNA Technique; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA fingerprinting; technika náhodné amplifikace polymorfní DNA; DNA bakterií; Bacterial Typing Techniques; DNA Fingerprinting